2012
DOI: 10.1177/1097184x12455398
|View full text |Cite
|
Sign up to set email alerts
|

From Sentimentality to Masculine Excess in Galician National Discourse

Abstract: This article studies the gendered meanings of Galician national discourse with particular focus on the notion of masculinity. The first part of the article analyzes cultural writings in the early stages of Galician regionalism and establishes how the metaphor of Galicia as feminine (and, as a consequence, of Galician manhood as marked with the notions of sentimentality and submissiveness) gradually became an important stumbling block for nationalism's emergence as a viable political movement. In the second sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Drawing on the initial debate in feminist academia focusing on this connection (Cockburn, 1998;Hasso, 1998;Herr, 2003), the study reveals a consensus among all interviewees that both concepts converge and become tools to achieve 'liberation' in a national and gender perspective. This statement, which has been argued by many authors (Queizán, 2004;Ortbals, 2007;Miguélez-Carballeira, 2012) in the Galician nationalist movement, remains contemporary. In part, these authors find this alliance reminiscent of post-colonial feminist theory (see chapter 2).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Drawing on the initial debate in feminist academia focusing on this connection (Cockburn, 1998;Hasso, 1998;Herr, 2003), the study reveals a consensus among all interviewees that both concepts converge and become tools to achieve 'liberation' in a national and gender perspective. This statement, which has been argued by many authors (Queizán, 2004;Ortbals, 2007;Miguélez-Carballeira, 2012) in the Galician nationalist movement, remains contemporary. In part, these authors find this alliance reminiscent of post-colonial feminist theory (see chapter 2).…”
Section: Discussionmentioning
confidence: 89%
“…However, the complexity of this process must be acknowledged where the wide context of an internal crisis (Nespereira Vale, 2017), the years of collective work by feminist groups and individuals (Ortbals, 2007;Miguélez-Carballeira, 2012) As previous studies about the feminisation of political movements observed (Tasdemir, 2013), the more women have the ability to manoeuvre, the more influence they will have to make changes regarding masculine structures, integrating feminist policies or creating safe decision-making spaces. The research findings have highlighted not only the importance of feminist leadership but especially the significance of the women activists' collective consciousness behind them.…”
Section: Discussionmentioning
confidence: 99%